"Towards GDP to GEP-Centric Model: A Proposed GEP Index Framework and Its Application in Haryana" (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: In the coming years, India’s developmental narrative is poised for a fundamental shift— from a traditional Gross Domestic Product (GDP)-driven model toward a more inclusive and empowerment-based framework of progress. This emerging paradigm is increasingly reflected in national policy discourse and statements by the Prime Minister, who emphasizes the need for a development approach centered on the Gross Empowerment of People (GEP) rather than solely on economic output. The concept of GEP underscores a multidimensional understanding of development that includes economic, social, political, digital, and cultural empowerment, moving beyond conventional growth metrics to focus on the real capabilities, freedoms, and dignity of individuals.This research paper investigates the theoretical foundations and practical significance of the GEP model as a guiding principle in India’s evolving development strategy. Recognizing the complexity of measuring empowerment, the study proposes a comprehensive and context-sensitive GEP Index, designed to capture the multidimensional nature of empowerment within India’s unique socio-political landscape.The research applies this proposed GEP Index to a detailed case study of the state of Haryana. Haryana presents a compelling case for analysis due to its paradoxical developmental profile: the state boasts one of the highest per capita incomes and robust industrial growth rates nationally, yet it continues to grapple with persistent social challenges, including gender disparities, high dropout rates in education, and significant rural-urban inequalities. These contradictions make Haryana an ideal laboratory to test the efficacy of the GEP Index in revealing the nuanced dimensions of empowerment that traditional economic indicators may obscure.Using a composite methodology that integrates quantitative data from government reports, surveys, and indices, alongside qualitative assessments of policy impacts, the study evaluates Haryana’s performance across five key dimensions of the GEP Index—economic empowerment, social empowerment, political participation, digital inclusion, and psychological and cultural empowerment. The findings highlight areas of strength, such as economic and digital empowerment, alongside critical gaps in social and cultural dimensions, particularly related to gender equality and educational access.The study concludes by discussing the implications of adopting a GEP-centric development framework for policymakers, emphasizing how such an approach can help bridge the gap between economic growth and genuine human development. It argues that the GEP Index offers a more holistic and equitable alternative to GDP, enabling governments to design targeted interventions that foster inclusive empowerment. Ultimately, this research contributes to the growing global and Indian discourse on redefining progress by offering a practical, measurable, and policy-relevant empowerment framework. It demonstrates that while Haryana exemplifies some of India’s economic successes, true development must be measured by the extent to which its people are empowered to participate fully in society and shape their own futures.